Organocatalytic Asymmetric Conjugate Additions to Cyclopent‐1‐enecarbaldehyde: A Critical Assessment of Organocatalytic Approaches towards the Telaprevir Bicyclic Core. Issue 52 (25th November 2015) - Bernardi, Luca; Fochi, Mariafrancesca; Carbone, Riccardo; Martinelli, Ada; Fox, Martin E.; Cobley, Christopher J.; Kandagatla, Bhaskar; Oruganti, Srinivas; Dahanukar, Vilas H.; Carlone, Armando
Abstract: In the context of a programme directed at the manufacture of telaprevir, eight possible approaches to its bicyclic α‐amino acid core, based on organocatalytic enantioselective conjugate additions to cyclopent‐1‐enecarbaldehyde, were identified and preliminarily explored. Four reactions, delivering advanced intermediates en route to the target amino acid, were selected for a thorough optimisation. Three of this reactions involved iminium ion catalysis with a prolinol catalyst (addition of nitromethane, nitroacetate and acetamidomalonate) and one was based on a Cinchona ‐derived phase‐transfer catalyst (addition of glycine imines). A careful choice of additives allowed lowering of the catalyst loading to 0.5 mol % in some cases. The preparation of intermediates that would give access to the core of telaprevir in good yields and enantioselectivities by exploiting readily available substrates and catalysts, highlights the potential of organocatalytic technology for a cost‐effective preparation of pharmaceuticals. Abstract : Organic bicycle : From a manufacturing perspective, eight organocatalytic approaches delivering advanced intermediates towards the challenging bicyclic amino acid core of telaprevir (see scheme) were identified and explored, highlighting the potential of organocatalytic technologies for a cost‐effective preparation of pharmaceuticals.